Pinus halepensis somatic embryogenesis is affected by the physical and chemical conditions at the initial stages of the process. Issue 3 (1st June 2016) - Pereira, Catia; Montalbán, Itziar Aurora; García-Mendiguren, Olatz; Goicoa, Tomás; Ugarte, Maria Dolores; Correia, Sandra; Canhoto, Jorge Manuel; Moncaleán, Paloma
Abstract: Pinus halepensis has been described as a drought-tolerant species with high plasticity to growth in different environments. Its eco-physiological characteristics could facilitate the use of this species in large afforestations in the future scenery of climate change. Somatic embryogenesis is a biotechnological tool with potential for large-scale clonal propagation. In order to establish an improved regeneration protocol for Pinus halepensis, the effects of different temperatures (18, 23, and 28 °C) and water availability conditions (2, 3, and 4 g L −1 Gelrite®), during initiation of embryonal masses on the rate of initiation, proliferation, maturation, and the number of embryos developed, were evaluated. It was found that environmental conditions during the initiation stage of Pinus halepensis somatic embryogenesis influence the success of initiation and proliferation. In contrast, there was no effect of these conditions on the maturation rates and the number of somatic embryos. Somatic embryos were obtained in all treatments tested, indicating that plants can be produced from extreme conditions of induction, such as high temperatures (28 °C) and low water availability conditions (4 g L −1 ).